Indium gallium zinc oxide layer used to decrease optical reflection loss at intermediate adhesive region for fabricating mechanical stacked multijunction solar cells. (6th December 2016) - Sameshima, Toshiyuki; Nimura, Takeshi; Sugawara, Takashi; Ogawa, Yoshihiro; Yoshidomi, Shinya; Kimura, Shunsuke; Hasumi, Masahiko
Abstract: Reduction of optical reflection loss is discussed in three mechanical stacked samples: top crystalline silicon and bottom crystalline germanium substrates, top crystalline GaAs and bottom crystalline silicon substrates, and top crystalline GaP and bottom crystalline silicon substrates using an epoxy-type adhesive with a reflective index of 1.47. Transparent conductive Indium gallium zinc oxide (IGZO) layers with a refractive index of 1.85 were used as antireflection layers. IGZO layers were formed on the bottom surface of the top substrate and the top surface of the bottom substrate of the three stacked samples with thicknesses of 188, 130, and 102 nm. The insertion of IGZO layers decreased the optical reflectivity of the stacked samples. The IGZO layers provided high effective optical absorbency of bottom substrates of 0.925, 0.943, and 0.931, respectively, for light wavelength regions for light in which the top substrates were transparent and the bottom substrates were opaque.